Emergency healthcare of the future. (June 2014) - FitzGerald, Gerry; Toloo, Ghasem (Sam); Romeo, Michele
Abstract Emergency healthcare is a high profile component of modern healthcare systems, which over the past three decades has fundamentally transformed in many countries. However, despite this rapid development, and associated investments in service standards, there is a high level of concern with the performance of emergency health services relating principally to system wide congestion. The factors driving this problem are complex but relate largely to the combined impact of growing demand, expanded scope of care and blocked access to inpatient beds. These factors are unlikely to disappear in the medium term despite the National Emergency Access Target. The aim of this article is to stimulate a conversation about the future design and functioning of emergency healthcare systems; examining what we understand about the problem and proposing a rationale that may underpin future strategic approaches. This is also an invitation to join the conversation.